Isolation of maltogenic amylase gene from bacillus licheniformis TH-1 - Jonet, Mohd Anuar (2007)
Amylases with unique properties have been isolated and characterized for various applications in starch industry. Among the amylolytic enzymes isolated, maltogenic amylase has been identified to hydrolyze cyclodextrin to maltotriose and maltose. The maltogenic amylase gene was isolated and cloned from a locallly isolated Bacillus licheniformis TH-1. Gene of about 1773bp encoding 591 amino acid sequence of maltogenic amylase was identified. Amino acid sequence of the maltogenic amylase from Bacillus licheniformis TH-1 showed the highest homology of 99%, with 99% identity to Bacillus licheniformis DSM 13.